2021
DOI: 10.1038/s41392-021-00669-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel dephosphorylation targeting chimera selectively promoting tau removal in tauopathies

Abstract: Intraneuronal accumulation of hyperphosphorylated tau is a hallmark pathology shown in over twenty neurodegenerative disorders, collectively termed as tauopathies, including the most common Alzheimer’s disease (AD). Therefore, selectively removing or reducing hyperphosphorylated tau is promising for therapies of AD and other tauopathies. Here, we designed and synthesized a novel DEPhosphorylation TArgeting Chimera (DEPTAC) to specifically facilitate the binding of tau to Bα-subunit-containing protein phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…14,15 DEPTAC was developed within the last year to reduce pathological levels of hyperphosphorylated tau protein. 13 Compared to less selective strategies relying either on kinase inhibitors or on phosphatase activators, this strategy brings protein phosphatase 2A-Bα (PP2A-Bα) in proximity to tau, in a conceptual design that resembles PROTACs. In essence, the DEPTAC molecule consists of a tau binding peptide fused by a linker to a PP2A-Bα-recruiting peptide and a C-terminal cell-penetrating peptide.…”
Section: Ups-dependent Intracellular Protein Degradation Is Mediated ...mentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 DEPTAC was developed within the last year to reduce pathological levels of hyperphosphorylated tau protein. 13 Compared to less selective strategies relying either on kinase inhibitors or on phosphatase activators, this strategy brings protein phosphatase 2A-Bα (PP2A-Bα) in proximity to tau, in a conceptual design that resembles PROTACs. In essence, the DEPTAC molecule consists of a tau binding peptide fused by a linker to a PP2A-Bα-recruiting peptide and a C-terminal cell-penetrating peptide.…”
Section: Ups-dependent Intracellular Protein Degradation Is Mediated ...mentioning
confidence: 99%
“…13 In an elegant series of proofof-concept experiments, the authors demonstrated that the DEPTAC bound to both tau and to PP2A-Bα in vitro, while a control chimera harbouring mutations in both of these domains did not. 13…”
Section: Ups-dependent Intracellular Protein Degradation Is Mediated ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tau hyperphosphorylation causes abnormal aggregation and neurodegeneration in AD brains [141], and protein phosphatase 2A (PP2A) has the most robust dephosphorylation activity to tau protein in vitro and in vivo [142]. A novel DEPho-sphorylation Targeting Chimaera (DEPTAC) was designed to enhance the combination of tau and PP2A-Bα, which shows high efficiency in preventing tau accumulation in vitro and in vivo [143]. Further studies showed that DEPAC significantly improved the microtubule assembly, neurite plasticity, and hippocampus-dependent learning and memory in transgenic mice [143].…”
Section: The Prospect Of Treatment Of Admentioning
confidence: 99%
“…A novel DEPho-sphorylation Targeting Chimaera (DEPTAC) was designed to enhance the combination of tau and PP2A-Bα, which shows high efficiency in preventing tau accumulation in vitro and in vivo [143]. Further studies showed that DEPAC significantly improved the microtubule assembly, neurite plasticity, and hippocampus-dependent learning and memory in transgenic mice [143].…”
Section: The Prospect Of Treatment Of Admentioning
confidence: 99%